La teoría económica espacial - Stavenhagen, Gerhard (1960)
The starting point of space economics studies is the location theory, created by THÜNEN (and completed by BRINKMANN) in the agricultural field and by WEBER in the industrial one, which was developed in isolation, just by the economic general theory. Further investigations extended initial perspectives, and so we have the contribution and theories of ROSCHER, SCHAFFLE, LAUNHARDT, SOMBART, GOTHEIN, ENGLANDER, PREDÜHL, CASEEI, RISTUHL, OHLIN, WEIGMANN, PALANDER and LÖSCH, whose conclusions form the present scope of space economic theory which, as an inseparable part of the whole economic theory, includes the problems of international trade.